2019
DOI: 10.1088/1361-6382/ab57b2
|View full text |Cite
|
Sign up to set email alerts
|

The Penrose inequality for perturbations of the Schwarzschild initial data

Abstract: We show that in the conformally flat case the Penrose inequality is satisfied for the Schwarzschild initial data with a small addition of the axially symmetric traceless exterior curvature. In this class the inequality is saturated only for data related to special sections of the Schwarzschild spacetime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 21 publications
(61 reference statements)
2
18
0
Order By: Relevance
“…This theorem generalizes partially that in [11], but now an analysis of nongeneric case is much more difficult. Note that data which satisfy conditions 1-3 of Definition 3.1 depend on one free function X.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…This theorem generalizes partially that in [11], but now an analysis of nongeneric case is much more difficult. Note that data which satisfy conditions 1-3 of Definition 3.1 depend on one free function X.…”
Section: Discussionsupporting
confidence: 62%
“…A review of results on existence theorems in different settings can be found in [15]. As in [11], we assume in this paper that g ij = δ ij and the initial surface is…”
Section: A Perturbative Formulation Of the Penrose Inequalitymentioning
confidence: 99%
See 3 more Smart Citations